Pengaruh Kualitas Pelayanan, Fasilitas, dan Lokasi terhadap Kepuasan Pengguna Jasa (Studi Kasus Pada Hotel Andelir Semarang) - Indriyatni, Lies; Kusuma, Putri Indah (STIE PENA, 2024)
This study aims to test whether the Quality of Service, Facilities, and Location affect Service User Satisfaction at Andelir Hotel Semarang. The population in this study was calculated from the average visit of Andelir Semarang hotel service users in the January-December 2021 period. Sampling using the Slovin formula obtained a total sample of 95 respondents. The sampling technique used is non-probability sampling with a purposive sampling approach. The types of data used are primary data and secondary data. This study uses questionnaires, observations, and interviews, in collecting data. The data analysis method used is quantitative analysis, namely by testing the validity and reliability, classic assumption test, multiple regression analysis, t test and F test and test the coefficient of determination with the help of SPSS version 25. The results of this study indicate that: Service Quality has a positive and significant effect on Service User Satisfaction. Facilities have a positive and significant effect on Service User Satisfaction. Location has a positive and significant effect on Service User Satisfaction. Service Quality, Facilities, Location jointly or simultaneously have a significant effect on Service User Satisfaction. The regression equation Y = -4.753+0.185 X1+0.216 X2 +0.156 X3 +e Keywords: Service Quality ; Facilities ; Location ; and Service User Satisfaction